Kepemimpinan Lokal dalam Pelestarian Budaya Buton pada Masyarakat Katobengke di Kota Bau-Bau - Muhammad Amir (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2013)
ABSTRACT This study aims to investigate the implementation of local leadership in community Katobengke, and evaluate the role of local leadership in the preservation of culture Buton. This study used qualitative research methods, with an ethnographic approach. What this study in three villages in the subdistrict Betoambari Katobengke Village, Village Lipu, and Village Waborobo. Informants in this study is parabela, the customs, and the village chief. Methods of data collection in this research are: the method of participant observation (partisipation observation method), in-depth interviews (interview method), and library research (library research). The method of data analysis is the analysis of qualitative data. The results until now still looks implementation of local leadership for community groups in the frame Katobengke formal authority-administrative leadership. Parabela obtain the source of authority from customary rules are still strongly attached in the community. Values - values and norms that have traditionally been handed down since the ancestors can be a reference for behavior in the social life of the citizens of the city of Bau-Bau heterogeneity without a negative view of one of the groups that the Katobengke in interacting with other townspeople Bau-Bau. These values are disseminated and transformed by parabela through customary institutions that have long proven Katobengke society to remain confident and continue to build cooperation with external parties is the Katobengke social capital, which can be an example for city residents others outside the community katobengke, because generally people of Bau-Bau has been heavily influenced by modern life, individualistic and with a range of conflict. The role of local leadership in cultural pelastarian buton still act as adat. Key words: local leadership, cultural preservation Buton, and Katobengke society